In scrubs and boots, the physician beyond the hospital: the experience of family medicine residents in an urban community - León Solarte, Maira Alejandra; Jaime Martínez, Nathalia Lucía (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2020)
Objective: To analyze the roles played by family medicine residents during their postgraduate training process, in the development of a community project at urban area of  Tunja city. Methodology: Qualitative study from the experience of resident doctors specializing in family medicine, within the framework of the community project as a training strategy. The information was collected in 2019 from 135 field records, which were provided with consent, and processed using qualitative content analysis techniques from registry units and participant observation. Conclusions: Practice in out-of-hospital settings, such as home, educational, and community settings are highly relevant for training in family medicine; who are clinical and social integrators. During postgraduate training, it is necessary to acquire the necessary job competencies to perform the various roles that the family doctor can perform, among which the clinical, educator, manager, researcher and community roles stand out.